Evaluation of the Coast Guard District Southwestern Mindanao (CGDSWM) Summer Lifeguard Training - Romel B. Dua (Future Science / FSH-PH Publications, 2026)
Whenever lifeguards are deployed as emergency responders in leisure swimming areas or during floods, drowning incidents are prevented. But too often than not, there are fewer or no lifeguards at all, risking safety assurance. When the Philippine Coast Guard was seasonally deployed on public beaches, this initiative was affected by human resources, financial logistics, and inconsistent implementation. As such, the Coast Guard District Southwestern Mindanao (CGDSWM) launched a Summer Lifeguard Training Program to capacitate coast guard personnel. After two successful trainings, no evidence-based evaluation has been made to support its effectiveness. Hence, this study examines the program’s effectiveness in terms of objectives, content, instructors, and facilities; evaluates lifeguard performance; and describes associated challenges to inform program improvements. Using surveys, document review, and interviews, the study collected data from 69 PCG-trained lifeguards, 65 supervisors and commanding officers, and 15 program implementers and course directors. Findings revealed a highly effective training program in developing essential lifeguard competencies, though improvements are needed in disaster-response coverage, instructional strategies, and simulation realism, with mean range scores from 3.46 to 3.55. The PCG-trained lifeguards were also rated with a consistently advanced level of competencies with a total mean score of 3.79, showing readiness for real-world emergency response and effective training transfer. Yet there are recurring structural, logistical, and resource challenges that affect its program outcomes. Thus, a proposed enhancement framework has been developed outlining recommendations for a systematic, participatory, and sustainable training program, fit for standardized and nationwide PCG adoption.